Detection of Goat Digestive Tract Protozoa Through Feces Examination in Kwanyar Sub-District, Bangkalan District - Meyreta Doti Alcaterana; Poedji Hastutiek; Nunuk Dyah Retno Lastuti; Endang Suprihati; Agus Sunarso (Journal of Parasite Science (JoPS), 2021)
This study aims to determine the prevalence and species of protozoa that infect theÂ digestive tract of goats in Kwanyar Sub-District, Bangkalan District. This study was conducted in June-July 2019 with 100 samples of stool examination in the laboratory of the Division of Parasitology, Faculty of Veterinary Medicine, Airlangga University. On examination found two types of protozoa, which were: Eimeria sp and Blastocystis sp. The results of this study showed the prevalence of 48% digestive tract protozoa. The results of statistical analysis using the Chi-Square test showed significant differences in age under one year and over one year in goats (p <0.05).